Ocimum tenuiflorum Linn. and Solanum nigrum Linn. Plant Extracts Possess Little to no Activity against Antibiotic Resistant and Susceptible Bacteria and are Non-toxic in vitro - Tiwana, Gagan; Cock, Ian E.; Cheesman, Matthew J. (Pharmacognosy Communications)
Background: Ayurvedic medicines have been used for thousands of years. Bacterial infections comprise the conditions that are treated by the plant-based medicinal therapy. Due to the increasing levels of bacterial resistance to antibiotics, new therapies are desperately needed, and Ayurvedic plants offer an alternative source of new treatment modalities in this regard. Aim: Two Ayurvedic plants, Ocimum tenuiflorum Linn. (OT) and Solanum nigrum Linn. (SN), have received little attention for their medicinal properties, particularly their antibacterial effects. This study sought to characterise the bacterial growth inhibitory properties of extracts from these plants, while also determining the toxicity of the extracts as well as their phytochemical profiles. Materials and Methods: Water, methanol and ethyl acetate extracts were prepared and antibacterial assays conducted on the extracts on agar and by using broth-based methodologies. The toxicities of extracts were measured using an Artemia franciscana lethality assay. The phytochemical constituents of each extract were subjected to LC-MS analysis so they could be compared to the results from the antibacterial assays. Results: No significant inhibition of any of the bacterial species (Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), Escherichia coli, extended-spectrum β-lactamase (ESBL) E. coli, Klebsiella pneumoniae, ESBL K. pneumoniae, Bacillus cereus, Shigella sonnei, Shigella flexneri, and Salmonella typhimurium) was observed. However, inhibition in broth was observed across most of these species for OT methanolic extracts, with MIC values ranging from 522 to 2338 μg/mL. The growth of only one species, B. cereus, was inhibited at a moderate level (1819 μg/mL). All other extracts showed little to no inhibition. The extracts were non-toxic in the Artemia franciscana lethality assays. A number of terpenoids and flavonoids were detected in the various extracts using LC-MS analysis and these results are discussed in context with the antibacterial properties of OT and SN. Conclusion: The lack of activity may be due to the poor quality or potency of the plant materials obtained from commercial suppliers: low concentrations of active constituents, solvent limitations, or possible synergistic effects lost in crude extracts. Further studies using authenticated plant materials from different suppliers, optimised extraction and testing protocols are recommended to more rigorously evaluate their antibacterial potential.
Keywords: Antimicrobial resistance; Ayurvedic medicinal plants; LC-MS analysis; Antibacterial activity; Phytochemicals; Toxicity.